PENGEMBANGAN APLIKASI SIKLUS AKUNTANSI DENGAN MICROSOFT EXCEL DENGAN PENDEKATAN SIKLUS TRANSAKSI - I Made Ariana (Valid: Jurnal Ilmiah, 2016)
The general objective of this research is to develop accounting cycle applications of services and trade company with transaction cycle approach by using Microsoft Excel and to know the ability of accounting cycle applications provide valid information. The model used in this study was adapted from the model of research and development (Research & Development) Borg & Gall modified in three stages: development of accounting cycle application by using Microsoft Excel with transaction cycle approach, assessment of applications by computer/accounting expert, and perform accounting cycle application testing. Results of this research is the accounting cycle applications with cycle transactions approach that were developed with the steps are: designing a cycle of transactions (purchases, sales, and cash), automate journal (purchases, sales, cash receipts, cash disbursements, general), general ledger and subsidiary ledger, the worksheet, financial statements, closing trial balance, data protection, application menu, and assessing and testing applications. Based on the test results can be known that the application of the accounting cycle with Microsoft Excel with transaction cycle approach can provide valid information